Bromeliaceae como ferramenta em estudos ambientais na Guarnição de Aeronáutica de Pirassununga (Pirassununga, SP) - Silva, José Victor da (2019)
The Cerrado is the second largest phytogeographical domain in Brazil, with its great territorial extension the Cerrado has great diversity of environmental conditions and consequently a great variety of vegetal formations.The vegetation formations of the Cerrado can be understood through the concept of "forest-ecotone-field", which shows a gradient between forest formations (cerradão) and field formations (clean field), between these formations occur the other Cerrado formations. Thanks to this diversity of plant formations with different environmental conditions, the Cerrado is home to a great biodiversity. Bromeliaceae is the largest restricted family in the Americas with about 3150 species, in Brazil there are 1370 species, the Cerrado has the second largest number of Bromeliads 253, in the Cerrado formations in the State of São Paulo 23 species occur. The Bromeliaceae family has as general characteristics its leaves arranged in rosettes, usually forming a tank and with spines, its roots in most species are used only for fixation, water absorption by most species of Bromeliaceae is given by their trichomes distributed in a manner varied in its leaves. The present study was carried out at the Aeronautical Garrison of Pirassununga (Pirassununga, SP), Garrison has about 1500 hectares of vegetation.In the first chapter the species of Bromeliaceae occurring in a cerradão area were mapped, identified and counted from their points of occurrence, seven species were identified and it was possible to notice that these species even having similar dispersion means (all species are dispersed by the wind except for Ananas) were distributed differently in space. It was discussed that this variety is due to differentmorphological characteristics of each species favoring its fixation in areas with different environmental conditions, so the occurrence and increase in the population of certain species of Bromeliaceae is directly influenced by the environmental conditions of a fragment, such as temperature and humidity. In the second chapter of this dissertation,the floristic survey of the family Bromeliaceae in the Garrison was carried out, where the different vegetal formations that occurred in the Garrison were sampled. It was recognized nine species of Bromeliaceae distributed in five genera, although not a very high number, comparing with other studies the number of species in the Garrison can be considered high. Finally the present work concludes that species of theBromeliaceae family occurring in an area can be directly affected by small variations in the microclimate conditions of a vegetal fragment, this work also concludes that the Garrison is an important area for the conservation of the biodiversity in the State of Sao Paulo.